Polymer Recycling: A Comprehensive Overview and Future Outlook - Paul van den Tempel; Francesco Picchioni (Recycling)
Polymer recycling is an essential and crucial topic in our sustainability-driven society. The depletion of oil and the increasing interest in biomass conversion clearly stimulate the search for alternative carbon sources. On the other hand, polymeric products (plastic, rubber etc.) are ubiquitous and are an integral part of our life. Recycling these products is thus of paramount importance, and perhaps crucially, from an environmental point of view. In this work, we will focus on the most common commodities, with the most important being (in terms of production volume) thermoplastics, rubbers and thermosets. A consequence of this choice is that the most common materials as well as chemical and biochemical recycling methods will be discussed. New advances in the corresponding technologies will be presented and critically evaluated. Finally, on the basis of this literature review, we will identify current trends and possible future developments.